White muscle disease in three selenium deficient beef and dairy calves in Argentina and Uruguay - Rodriguez, Alejandro Martin; Schild, Carlos Omar; Canton, German Jose; Riet-Correa, Franklin; Armendano, Joaquín Ignacio; Caffarena, Rubén Dario; Brambilla, Emilio Cesar; García, Juan Agustín; Morrell, Eleonora Lidia; Poppenga, Robert; Giannitti, Federico (Centro de Ciências Rurais, Universidade Federal de Santa Maria, 2018)
White muscle disease (WMD), nutritional myodegeneration or enzootic muscular dystrophy, is a nutritional condition associated with selenium and/or vitamin E deficiency in ruminants. These elements are constituents of the major body antioxidant systems. Depletion of selenium results in oxidative damage to cardiac and skeletal muscle cells, resulting in myodegeneration and myonecrosis, typical lesions of WMD. Selenium deficiency is common in South America, but WMD is underreported. This research describes clinical, biochemical and pathological findings in two episodes of WMD associated with selenium deficiency in beef and dairy calves in Argentina and Uruguay with concurrent copper deficiency in one of them, which resulted in spontaneous calf mortality. Further studies are necessary to estimate the true incidence and economic impact of clinical and subclinical mineral deficiencies in livestock production systems in the southern cone of South America.